PEKERJA SEKS KOMERSIAL (PSK) DAN TANGGUNG JAWAB PIDANA DALAM ERA PROSTITUSI ONLINE - Andi Zulfa Majida; A.Irwan Hamzani; Sururi, Sururi; Moh Khamim (Journal of Innovation Research and Knowledge, 2024)
The use of modus operandi in criminal activities evolves alongside human civilization, as seen in the transition of prostitution from conventional to online platforms. In conventional prostitution, pimps profit by selling sex workers, whereas in online prostitution, sex workers take initiative in selling themselves. Consequently, the legal status and responsibilities of sex workers in online prostitution remain unclear within Indonesia's positive law. This study employs a normative approach, utilizing legislative and conceptual analyses to assess the legal status and responsibilities of sex workers in online prostitution. The research findings indicate that while sex workers in online prostitution are not categorized as victims according to the law, they cannot be prosecuted due to the absence of criminal elements. Additionally, they cannot be subjected to punishment under local regulations governing prostitution, as this would contradict the legal principle of lex superior derogat legi inferior